Melt - Hardt, Helen (Hardt, Helen. Steel brothers saga, 2016)
Jonah Steel is intelligent, rich, and hard-working. As the oldest of his siblings, he was charged by his father to protect them. He failed in the worst way. Dr. Melanie Carmicheal has her own baggage. Although the renowned therapist was able to help Jonah's brother, she is struggling with feelings of inadequacy. When the oldest Steel walks into her office seeking solace, she can't turn her back. As Melanie and Jonah attempt to work through their issues together, desperately trying to ignore the desire brewing between them, ghosts from both their pasts surface...and danger draws near.